Tantangan Penatalaksanaan STEMI di Pandemi Covid-19 - Sunanto Ng; Dafsah Arifa Juzar (The Indonesian Heart Association, 2020)
The necessity of timely management of ST-elevation myocardial infarction (STEMI) is now disrupted by the Covid-19 pandemic. This paper discussed the challenge to manage STEMI in Indonesia due to Covid-19. It also discussed the alternative strategies for solution. Challenge can occur in term of the healthcare safety as well as STEMI patient safety. Healthcare safety potentially impaired by the problem of STEMI mimicry due to cardiovascular complication of Covid-10, inaccuracy of Covid-19 screening, lack of effective personal protection equipment for the healthcare and appropriate catheterisation laboratory to anticipate virus contamination. The safety of STEMI patient is potentially impaired due to prolonged ischemia time, and the risk of cross-infection. Solution for this challenge should include mass screening, rapid and accurate test to rule-out Covid-19, dual system of hospital units - Covid and non-Covid, and algorithm for triage patients with STEMI and Covid-19.